Sonerila victoriae, a new species of Melastomataceae from Southern Western Ghats, India - Soumya, Murugan; Rampradeep, Rajamani; Jisha, Kunnamkumarath; Arabhi, Pathiyil; Rekha, Vasudevan Ambat; Nair, Maya Chandrasekharan (Phytotaxa, 2017)
A new species, Sonerila victoriae, collected from Pothumala of Nelliyampathy hill ranges of Western Ghats of Kerala, India is described and illustrated. It shows similarity with Sonerila wallichii and Sonerila gadgiliana, but differs in traits regarding the size, shape and texture of leaves, number of inflorescence per plant, number of flowers per inflorescence, shape of anther, texture and morphology of seed.